Pengaruh Penyuluhan Pendidikan Kesehatan Tentang HIV/AIDS Terhadap Pengetahuan Siswa Kelas X di SMA Namira Medan Tahun 2022 - Rianita Siagian (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
HIV stands for Human Immunodeficiency Virus, a virus which weakens immune system, while Acquired Immune Deficiency Syndrome (AIDS) is a collection of disease symptoms due to decreased immunity, which are acquired (not genetic). Education about HIV/AIDS to reduce the incidence rate of, because so far there is no medication or vaccine to prevent the spread of HIV/AIDS. To date, health education extension in order to enhance knowledge of HIV/AIDS is quite successful. The attempt to increase knowledge for formal and informal education as well as general and religious education is made by integrating HIV/AIDS materials systematically. The results of preliminary study on 10 students indicated that 40% (four student)can answer more than five questions , and 60 % ( 6 students ) can only be answered fewer than five questions investigators.Objective: To identify the effects of health education extension about HIV/AIDS on knowledge in tenth grade students at SMA Namira Medan Tahun 2022. Methods: This research employed a Quasi Experiment Design with one group pretest-posttest. Subjects of the research were tenth grade students of SMA Namira Medan. Sampling employed purposive sampling with a sample size of 40 students. Hypothesis was analyzed using statistical test, namely Wilcoxon test. Results: The Wilcoxon test indicated that there were significant differences in knowledge with p value of<0.05 (p = 0.001) and Z >1,96 (Z=3,212). Conclusion: There are effects of health education extension about HIV/AIDS on the knowledge of tenth grade students of SMA Namira Medan Tahun 2022 as indicated with p <0.05 (p =0.001) and Z >1,96 (Z=3,212). Keywords: extension, knowledge, HIV/AIDS